Analysis of The Influence of Road Handling Based on Technical and Policy Factors on Provincial Roads in Sidoarjo - Akbar, Sutan Fahreza; Patriadi, Andi; Sajiyo (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
East Java Provincial Roads are vital infrastructure that supports the economic and social activities of the community. However, various road conditions, ranging from light to severe damage, are serious obstacles to the smooth running of transportation and economic activities. Limited maintenance budgets and increasing traffic burdens further exacerbate this problem. Therefore, determining the priority of road handling is a crucial step to ensure the effectiveness of the use of the budget and optimize the benefits for the community. Based on previous research, the determination of road handling priorities uses Multi-Criteria Analysis. This research aims to determine the priorities for handling roads in East Java Province by considering various factors. Influence factors will be divided into two major parts, namely policy factors and technical factors. What is considered in the policy factor is the conformity with the Strategic Plan of the East Java Provincial Public Works Office (Renstra) which contains the Priority Areas Policy for Development and the Regional Spatial Plan Policy (RTRW). For technical factors, considerations include road width, road stability conditions, traffic volume conditions, and degree of saturation. The results of the research are expected to be recommendations for local governments in formulating more effective and sustainable road management policies.